2019
DOI: 10.1113/jp277985
|View full text |Cite
|
Sign up to set email alerts
|

End‐diastolic force pre‐activates cardiomyocytes and determines contractile force: role of titin and calcium

Abstract: Titin functions as a molecular spring, and cardiomyocytes are able, through splicing, to control the length of titin. We hypothesized that together with diastolic [Ca2+], titin‐based stretch pre‐activates cardiomyocytes during diastole and is a major determinant of force production in the subsequent contraction. Through this mechanism titin would play an important role in active force development and length‐dependent activation. Mutations in the splicing factor RNA binding motif protein 20 (RBM20) result in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…These differences may partly contribute to the contraction properties of LV and RV myofilaments described by Belin et al (2011) , in addition to the differences in myofilament phosphorylation they observed. Titin isoform composition could play a role in the kinetics and extent of contraction, as we recently showed ( Najafi et al, 2019 ). Furthermore, LV versus RV differences have been found in terms of ion channel make-up and regulation ( Gaborit et al, 2007 ; Molina et al, 2016 ; Zaitsev et al, 2019 ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These differences may partly contribute to the contraction properties of LV and RV myofilaments described by Belin et al (2011) , in addition to the differences in myofilament phosphorylation they observed. Titin isoform composition could play a role in the kinetics and extent of contraction, as we recently showed ( Najafi et al, 2019 ). Furthermore, LV versus RV differences have been found in terms of ion channel make-up and regulation ( Gaborit et al, 2007 ; Molina et al, 2016 ; Zaitsev et al, 2019 ).…”
Section: Discussionmentioning
confidence: 71%
“…Titin isoform composition could play a role in the kinetics and extent of contraction, as we recently showed (Najafi et al, 2019). Furthermore, LV versus RV differences have been found in terms of ion channel make-up and regulation (Gaborit et al, 2007;Molina et al, 2016;Zaitsev et al, 2019).…”
Section: Contractile Differences Between Ventricular Regionsmentioning
confidence: 80%
“…Global LV function was estimated by means of transthoracic echocardiography (TTE) with the use of ultrasound system "Samsung Medison HM70" (Samsung, Korea), at rest and immediately after test (within 3 minutes of recovery period) according to ACC/AHA Guidelines for the Clinical Application of Echocardiography (2013) [19]. The following parameters were chosen as measures of global function: end-diastolic volume (EDV, ml), stroke volume (SV, ml), ejection fraction (EF, %), end-diastolic index (EDI, ml/m2), stroke index (SI, ml/m2) [20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…A significant addition to the longstanding knowledge on oblique and circumferential fibers was provided by Lunkenheimer et al, who provided evidence for the existence of transmural myofibres that may be of fundamental relevance to the regulation of forces associated with normal myocardial contraction and relaxation [19]. Finally, there is important structural diversity on the myocyte level that contributes to the overall elasticity of the cardiomyocyte, as revealed by different isoforms of the giant protein titin, which may influence myocardial deformation in systole and diastole, not least during exercise [20,21]. Collectively, the current knowledge indicates a non-uniform, complex mesh of diverse cardiac myofibre arrangements which may be grouped in sheets and laminae, influencing the electrical activation sequence of the heterogeneously distributed autonomic nerves in the heart (Figure 1, [22]).…”
Section: Anatomymentioning
confidence: 99%